Promotive role of MBNL3 and PXN genes expressions with lncRNA PXN-AS1-L on gastric cancer - Mai A.H. Abouelenin; Amany A. Saleh; Naglaa S. Elabd; Osama Elbahr; Reham Ahmed Abdelaziz; Mohammed G. Elhelbawy; Zeinab A. Kasemy; Ahmed Abdelkhalek Hussein; Mona A. Abbas (Biochemistry and Biophysics Reports, 2025)
Background: Gastric cancer ranks fourth in both incidence and mortality worldwide. Several genes influence its genesis and progress. Materials and methods: The expression of MBNL3, PXN genes, and lncRNA PXN-AS1-L was evaluated in gastric tissue samples from 75 gastric cancer patients and 75 controls by RT-PCR. Results: MBNL3, PXN, and lncRNA PXN-AS1-L expressions were considerably raised among cancerous gastric tissue than in nearby normal tissue and normal tissue from controls (p < 0.001). LncRNA PXN-AS1-L and MBNL3 had the highest sensitivity (92.00 % and 90.67 %, respectively), with PXN sensitivity of 81.33 % for differentiation of the cancer tissue from adjacent normal tissue, while PXN and lncRNA PXN-AS1-L had the highest sensitivity (98.67 % and 92.00 %, respectively), with 89.33 % for MBNL3 as discriminators between gastric cancer tissue and normal tissue from controls. Between metastatic and non-metastatic patients, MBNL3 and PXN were the highest differentiating markers (sensitivity = 87.50 % and 83.33 %, respectively). MBNL3, PXN, and lncRNA PXN-AS1-L were reliable predictors of gastric cancer (p = 0.004, p = 0.009, and p = 0.001, respectively), but only MBNL3 and lncRNA PXN-AS1-L were significant predictors for mortality (p = 0.026 and p = 0.043, respectively). The elevated expressions were linked to lower overall and progression-free survival rates. Conclusion: MBNL3, PXN, and lncRNA PXN-AS1-L expression levels can diagnose and predict gastric cancer and discriminate between metastatic and non-metastatic patients. The expression level of MBNL3 and lncRNA PXN-AS1-L can predict gastric cancer mortality. Higher expression of MBNL3 and PXN was linked to aggressive gastric cancer and low overall and progression-free survival rates.